Portas de entrada para a saída do inferno : a rede de serviços de atenção a mulheres em situação de violência - Brasilino, Jullyane Chagas Barboza (2014)
The present study aims to understand how policies to combat domestic violence against women create (or not) the necessary/sufficient support for them to leave the violence situation. The theoretical framework is based on critical positions in the Social Psychological field, Post-Constructionist and Feminist theories. It is taken into account that violence against women is a complex situation, in which several factors are included, such as social-economic conditions, educational level, family bounds and living conditions, among others. The research followed two steps. At first, the network to combat domestic violence against women in São Paulo/SP was descripted in three different moments: 1) initial strategies focused on combat, from 1983 to 1990; 2) the progressive enhancement of the network, from 1990 to 2006 and 3) the enlargement of the network after the Maria da Penha law. For that description, documents were used and observations were conducted in several services, as well as in events and public acts. At the second step, these observations were improved by interviews with women who were attended by the network services and technicians who had being working in the services. The experiences reported by women show that it is a difficult process to find an exit to the violence situation. The Government develops actions focused on the implementation of public policies for gender equity and the end of domestic violence, but that hasn t been enough, meaning that this issue requires more than a judicialization process. The research s results can be clustered around three axis: 1) judicialization gives women the possibility to punish the actor of violence and to prevent new acts of aggression, however, it s not enough to end the violence situations; 2) it has been identified that women in violence situation do not see themselves as people with rights and with the right to live free of violence; 3) the services network that serves women in violence situation has a fundamental role in the comprehension of these women as individuals with rights and, therefore, it should receive more attention and investment from the administration; it must be strengthened initially through public policies focused on gender equity